2017
DOI: 10.3102/0002831217716084
|View full text |Cite
|
Sign up to set email alerts
|

Short Intervention, Sustained Effects: Promoting Students’ Math Competence Beliefs, Effort, and Achievement

Abstract: Gewährt wird ein nicht exklusives, nicht übertragbares, persönliches und beschränktes Recht auf Nutzung dieses Dokuments. Dieses Dokument ist ausschließlich für den persönlichen, nicht-kommerziellen Gebrauch bestimmt. Die Nutzung stellt keine Übertragung des Eigentumsrechts an diesem Dokument dar und gilt vorbehaltlich der folgenden Einschränkungen: Auf sämtlichen Kopien dieses Dokuments müssen alle Urheberrechtshinweise und sonstigen Hinweise auf gesetzlichen Schutz beibehalten werden. Sie dürfen dieses Dokum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 70 publications
3
79
0
11
Order By: Relevance
“…Other prior task-value-focused interventions, implemented by researchers in science and math, also have increased students’ competence-related beliefs (Brisson et al, 2017; Canning & Harackiewicz, 2015; Hulleman et al, 2017). Those researchers discussed how students’ competence beliefs and task values are positively related, and so an intervention designed to enhance one might actually affect the other in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Other prior task-value-focused interventions, implemented by researchers in science and math, also have increased students’ competence-related beliefs (Brisson et al, 2017; Canning & Harackiewicz, 2015; Hulleman et al, 2017). Those researchers discussed how students’ competence beliefs and task values are positively related, and so an intervention designed to enhance one might actually affect the other in some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…First, in comparing interventions, stronger side effects were expected for interventions that show stronger effects on motivation in the target subject. With respect to our study, the quotations condition was shown to be more successful in promoting motivation in math (Brisson et al, 2016;Gaspard, Dicke, Flunger, Brisson, et al, 2015) and therefore was expected to also show stronger side effects. Second, regarding different outcomes, stronger side effects should be found for those motivational variables that are more effectively promoted in the target subject.…”
Section: Present Investigationmentioning
confidence: 90%
“…In these analyses, we controlled for the respective construct at the pretest in all three subjects to achieve more precise estimates of the intervention effects (Raudenbush, 1997). Effects on value and selfconcept in math as the target subject of the intervention have already been reported by Gaspard, Dicke, Flunger, Brisson, et al (2015) and Brisson et al (2016). For value, previous analyses used a more differentiated measure with subscales FIGURE 1.…”
Section: Intervention Effects On Value Self-concept and Effort In Mmentioning
confidence: 93%
“…Based in expectancy-value theory (Eccles et al 1983;Eccles and Wigfield 2002), relevance interventions aim at improving academic outcomes by raising students' beliefs about the utility value of an academic task or subject, that is its perceived usefulness to a student's current or future goals. Numerous correlational studies have shown that students who perceive the learning contents as highly useful feature high levels of interest and attainment values, self-efficacy beliefs and ability perceptions, as well as effort (for overviews, see e.g., Roeser et al 2000;Wigfield et al 2017; for correlations in the current sample, see Brisson et al 2017;Gaspard et al 2015a). Accordingly, fostering students' utility value beliefs in targeted interventions may lead to positive effects on other important academic outcomes.…”
Section: Theoretical Background and Effectiveness Of Relevance Intervmentioning
confidence: 86%
“…In addition, identifying the features of highly and lowly responsive students or classrooms, respectively, helps to unravel if certain students stick less to the instructions than others and to optimize the intervention materials accordingly. The current study addresses these gaps in research by using data from the intervention study "Motivation in Mathematics" (MoMa), which was shown to foster students' value and competence beliefs, effort, and achievement in mathematics-particularly for females (Gaspard et al 2015a;Brisson et al 2017). By analyzing students' essays on the relevance of mathematics written during the classroom intervention, the current study aims at: (a) providing a theory of change to assess and combine the core elements of students' responsiveness to the intervention activities, and (b) exploring individual student characteristics and classroom perceptions as predictors of student responsiveness.…”
Section: Introductionmentioning
confidence: 99%